2017
DOI: 10.1109/tnsre.2017.2681691
|View full text |Cite
|
Sign up to set email alerts
|

Regularized Speaker Adaptation of KL-HMM for Dysarthric Speech Recognition

Abstract: This paper addresses the problem of recognizing the speech uttered by patients with dysarthria, which is a motor speech disorder impeding the physical production of speech. Patients with dysarthria have articulatory limitation, and therefore, they often have trouble in pronouncing certain sounds, resulting in undesirable phonetic variation. Modern automatic speech recognition systems designed for regular speakers are ineffective for dysarthric sufferers due to the phonetic variation. To capture the phonetic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Our experimental results demonstrated that CLSTM-RNN has the potential to improve the ASR performance as a speaker-independent acoustic model for the patients with ALS. To further improve the ASR accuracies, techniques for session/speaker variability compensation including acoustic feature transformation [25,26], acoustic model adaptation [27], and pronunciation variation modeling [27,28] can be further applied. We speculate that the results may improve once a larger training dataset from more ALS patients is obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experimental results demonstrated that CLSTM-RNN has the potential to improve the ASR performance as a speaker-independent acoustic model for the patients with ALS. To further improve the ASR accuracies, techniques for session/speaker variability compensation including acoustic feature transformation [25,26], acoustic model adaptation [27], and pronunciation variation modeling [27,28] can be further applied. We speculate that the results may improve once a larger training dataset from more ALS patients is obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach presents a possibility in effectively modeling dysarthric speech (even low intelligible speech) in a speaker-independent way. Future directions include 1) a test of the CLSTM-RNN approach using a larger dataset collected from more subjects, 2) applying speaker adaptation/normalization techniques [27], and 3) using articulatory information [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…System References Model Hybrid [74], [75], [113], [141], [153], [154], [168], [178]- [180], [195], [212], [213], [230], [240], [284]-[290] E2E…”
Section: Levelmentioning
confidence: 99%
“…Korean Phonetically Optimized Words (KPOW) databas, Korean Phonetically Balanced Words (KPBW) database, Korean Phonetically Rich Words (KPRW) database and SI dysarthria adaptation were used for dysarthtic speech recognition with KL-HMM and compared with GMM-HMM and DNN-HMM. The framework of KL-HMM showed that is effective for dysarthric speakers to improve the performance [29].…”
Section: Related Workmentioning
confidence: 99%